Head impact situations in professional football (soccer) - Beaudouin, F.; Demmerle, D.; Fuhr, C.; Tröß, T.; Meyer, T. (Sports Medicine International Open, 2021)
To assess head impact incidents (HIIs) and to distinguish diagnosed head injuries from other incidents, a video observation analysis of match HIIs was conducted in the German Bundesliga (2017/18 season). Video recordings of each match were screened to identify the respective events. Head injury data were identified by a prospective injury registry. HII and head injury incidence rates (IR) were calculated with 95% CIs. The total number of HIIs was 1,362 corresponding to an IR of 134.9/1000 match hours (95% CI 127.9-142.2). In 123 HII (IR 12.2, 95% CI 10.2-14.5) the contact was classified as severe. Head contact with the opponent was the most frequent cause (85%). The most frequent mechanism was in 44% (combined) the arm and elbow-to-head, followed by head-to-head and hand-to-head contacts (each 13%). In 58%, the HIIs occurred during header duels. Twenty-nine head injuries were recorded (IR 2.9, 95% CI 2.0-4.1). Concussions/traumatic brain injuries accounted for 48%, head/facial fractures 24%, head/facial contusions 21%, and lacerations/abrasions 7%. The number of HIIs not classified as concussions/more severe trauma was high. Identification of HIIs and head injury severity should be improved during on-field assessment as many head injuries might go unrecognised based on the large number of HIIs.